The Factor Affecting to Profitability of Bank Mandiri (Persero) Tbk. Period 2011-2020 - Harjayanti, Diana Riyana; Irma, Ade; Safariningsih, Ratna Tri Hari; Kosasih, Fajar Gumilang (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
The purpose of this study is to determine factors Capital Adequacy Ratio, Non-Performing Loans and Operational Cost of Operating Income, Return On Assets as profitability at PT. Bank Mandiri (Persero) Tbk. with periode 2011-2020. The research method used in this study is descriptive quantitative. The population used is the financial statements of PT. Bank Mandiri (Persero) Tbk. The sample used is data that comes from the notes to the financial statements and income statements of PT. Bank Mandiri (Persero) Tbk. in the period 2011 to 2020. Based on the results of the partial test (t test) the results is Capital Adequacy Ratio and Non Performing Loan have not a significant influence on Return On Assets and Operational Cost of Operating Income has a significant influence on Return On Assets. But base on simultan (F test) shows that the Capital Adequacy Ratio, Non Performing Loan and Operational Cost of Operating Income have a significant influence on Return On Assets. In the coefficient of determination, the value of Adjusted R Square is 92.60%, Return On Assets can be explained by the Capital Adequacy Ratio, Non-Performing Loans and Operating Cost of Operating Income, which means that the relationship between variables has a strong correlation, while the remaining 7.4% can be explained by other variables.